PELATIHAN DAN PENDAMPINGAN PENYANDANG DISABILITAS DESA SIMBATAN, KECAMATAN NGUNTORONADI KABUPATEN MAGETAN - Mulyati, Tatik; Rohmatiah, Ahadiati; Amadi, Dwi Nor (Jurnal Terapan Abdimas, 2019)
Abstract. Based on data collected by the Government of Simbatan Village, Nguntoronadi Subdistrict, Magetan Regency in 2017, there are 39 people with disabilities in the village and 32 productive potential people were dominated by persons with intellectual disabilities. The purpose of this community service’s activity is to help people with intellectual disabilities and other disabilities in improving their skills and welfare. The steps of the activities are: 1. Facilitating the availability of materials, equipment and facilities needed for business capital of persons with disabilities; 2. Provide skills training and production of goods that can be made by persons with disabilities; 3. Ensure the sustainability of the business that has been initiated and developed; 4. Creating employment and data collection for persons with disabilities; and 5. Increasing business welfare and independence for persons with disabilities.The development of service activities is carried out by pioneering and making various types of skills / businesses that are artistic, economical and market oriented that can help provide employment opportunities for persons with disabilities through various business / production of goods, thus gaining income to meet their daily needs. Productive economic activities carried out by persons with disabilities are: 1. Making batik spattered (batik ciprat); 2. Making various handicrafts from various used plastic containers and patchworks; 3. Training in skills and other businesses according to market needs that can be done by persons with disabilities. Abstrak. Berdasarkan data yang dikumpulkan oleh Pemerintah Desa Simbatan, Kecamatan Nguntoronadi, Kabupaten Magetan pada tahun 2017, ada 39 orang penyandang cacat di desa tersebut dan 32 orang berpotensi produktif didominasi oleh orang-orang dengan cacat intelektual. Tujuan kegiatan pengabdian masyarakat ini adalah untuk membantu orang-orang dengan cacat intelektual dan cacat lainnya dalam meningkatkan keterampilan dan kesejahteraan mereka. Langkah-langkah kegiatannya adalah: 1. Memfasilitasi ketersediaan bahan, peralatan, dan fasilitas yang dibutuhkan untuk modal bisnis para penyandang cacat; 2. Memberikan pelatihan keterampilan dan produksi barang yang dapat dibuat oleh para penyandang cacat; 3. Memastikan keberlanjutan bisnis yang telah dimulai dan dikembangkan; 4. Menciptakan lapangan kerja dan pengumpulan data untuk para penyandang cacat; dan 5. Meningkatkan kesejahteraan bisnis dan kemandirian bagi para penyandang cacat. Pengembangan kegiatan layanan dilakukan dengan memelopori dan membuat berbagai jenis keterampilan / bisnis yang berorientasi artistik, ekonomis dan berorientasi pasar yang dapat membantu menyediakan peluang kerja bagi para penyandang cacat melalui berbagai bisnis / produksi barang, sehingga memperoleh penghasilan untuk memenuhi kebutuhan sehari-hari mereka. Kegiatan ekonomi produktif yang dilakukan oleh para penyandang cacat adalah: 1. Membuat batik ciprat (batik ciprat); 2. Membuat berbagai kerajinan dari berbagai wadah plastik bekas dan tambal sulam; 3. Pelatihan keterampilan dan bisnis lain sesuai dengan kebutuhan pasar yang dapat dilakukan oleh para penyandang cacat.